E-Business and E Commerce management : - Dave, Chaffey (Pearson, 2011)
This bestselling textbook offers a comprehensive introduction to the theory and practice of e-business and e-commerce management. The author, Dave Chaffey, brings his trademarks of authority, clarity of expression and teaching expertise to bear on a subject in which he actively lectures and consults.